Developing of character science teaching tools integrated with the value of Qur'an for junior high school students - Muhammad Irwansyah; Magfirah Perkasa; Muchlis Muchlis; Bakhtiar Bakhtiar; Nikman Azmin (Biology Education Department, IKIP Budi Utomo, Malang, Indonesia, 2021)
The curriculum of 2013 places spiritual attitudes as the first competencies from core competencies and social attitudes as the second. This indicates that a spiritual and social attitude is needed to survive in the 21st century. Therefore, this study was held with the aim to develop science teaching materials with integrated character of the Qur'anic verses that valid and effective criteria. The type of research that used in this research is adapted from Thiagarajan’s developing model which focused on defining, designing, and developing stages. The instruments used are validation sheets for expert judgement and student response questionnaires to collect spiritual character of the students. Based on the results of the study, the science teaching materials with Islamic character interpretations meet the valid criteria with the validity of RPP = 3.37, modules = 3.23 and LKS = 3.51. Meanwhile, based on the results of limited trials, it can be concluded that the students' responses to science teaching materials with integrated character of the Qur’anic verse are in the positive and very positive category.